Optimal connection of wind turbines to distribution grid to minimize power loss - Dinh Chung Phan; Ngoc An Luu (International Journal of Electrical and Computer Engineering (IJECE), 2023)
This research aims to connect wind turbines to a distribution grid to minimize the power loss and to satisfy the grid’s normal operating condition. The proposed algorithm will determine optimal positions, optimal operation mode and wind turbine type. We must choose the best operation mode from available modes including the constant power factor mode and the constant voltage mode. According to the optimal operation mode, we decide the optimal setting data of wind turbine. This algorithm is coded in MATLAB software and implemented to IEEE 33-buses distribution grid. Noted that in this research, we tested two cases including the original IEEE 33-buses grid and its modification where the power system connected to this grid at multi-position. Results indicated that the proposed algorithm could determine the number of wind turbines, position, optimal operation mode, wind turbine type and the priority order of wind turbine installation to minimize power loss. Moreover, results were also compared to that of other algorithms.